Factors affecting youth empowerment and entrepreneurial initiatives: Social implications and way forward - Javeed, Anam; Aljuaid, Mohammed; Mehmood, Sajid; Khan, Muhammad Yar; Mahmood, Zahid; Shahid, Duaa; Wali, Syed Sikandar (Frontiers in Psychology, 2022)
The purpose of carrying out this study is to probe into the fact that which of the factors impact the empowerment of Pakistani youth and its entrepreneurial initiatives in Pakistan. The study provides the model of the factors which could impact the empowerment of the youngsters. The model is extendable to other contexts as well and other factors can be added. The analytical findings could also help the government to take the social responsibility of underserved youth and indulge the youngsters in the policy making process so that such factors could be taken care of which are supposed to hinder the empowerment and their motivation to take entrepreneurial initiatives.